2020
DOI: 10.3390/pr8121644
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Approach to Thermal Production of New Materials from Asphaltenes of Castilla Crude Oil

Abstract: Asphaltenes are compounds present in crude oils that influence their rheology, raising problems related to the extraction, transport, and refining. This work centered on the chemical and structural changes of the asphaltenes from the heavy Colombian Castilla crude oil during pyrolysis between 330 and 450 °C. Also, the development of new strategies to apply these macromolecules, and the possible use of the cracking products as a source of new materials were analyzed. The obtained products (coke, liquid, and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Based on the results of numerous studies [1,[30][31][32][33], it is known that the structural unit of resinous-asphaltene substances is condensed benzene rings with heteroatoms, forming a flat geometric figure with side substituents in the form of alkyl chains and naphthenic rings. Located parallel to each other, such structures form microassociates (packs, globules, micromicelles), separated from each other by an oil layer.…”
Section: Rheological Characteristics Of Binary Bitumen-additive Systemsmentioning
confidence: 99%
“…Based on the results of numerous studies [1,[30][31][32][33], it is known that the structural unit of resinous-asphaltene substances is condensed benzene rings with heteroatoms, forming a flat geometric figure with side substituents in the form of alkyl chains and naphthenic rings. Located parallel to each other, such structures form microassociates (packs, globules, micromicelles), separated from each other by an oil layer.…”
Section: Rheological Characteristics Of Binary Bitumen-additive Systemsmentioning
confidence: 99%
“…It is worthy to note that asphaltenes are considerably believed to be a potential and perspective source of producing new raw materials. Afanasjeva et al [5] presented a mechanistic approach for the thermal production of new materials from asphaltenes of castilla crude oil. The authors found that the pyrolysis process at 330 and 450 • C can be used as an easy route to attain new materials associated with specific structural units from the asphaltenes.…”
mentioning
confidence: 99%